Investigation of some mechanisms for formation of exciton absorption bands in layered semiconductor n-InSe and p-GaSe crystals - Zhirko, Yu.I.; Zharkov, I.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
We show that processes of creation, radiation and decay of the ground (n = 1) and excited exciton states in layered n-InSe and p-GaSe crystals involve direct (photon -> exciton -> photon, at k = 0), as well as indirect vertical (photon ± phonon -> exciton -> photon ± phonon, at k ~0), optical transitions. For the n = 1 exciton state both transitions are compatible. For the excited exciton states the above transitions are not compatible; as a result, the integral intensity of absorption bands for excited exciton states, Kn, exceeds K⁰/n³ (where K⁰ is the classic value for the n = 1 exciton absorption band) and grows with temperature. It is shown that presence of two-dimensional gas of charge carriers (electrons/holes localized in quantum wells) that are degenerate with excitons in the momentum space leads to suppression of the oscillator strength of exciton transition for ground, as well as excited, states. It was found experimentally that growth of temperature in p-GaSe crystals results in holes redistribution to the higher-energy states. This appears as consecutive (from the ground to excited states) suppression and re-establishment of the integral characteristics of exciton absorption bands.